Analisis Kasus Pertambangan Panas Bumi pada Putusan Pengadilan Nomor 529/Pdt.G.Arb/2018/Pn.Jkt.Sel - Gita Silva Pramesti (Savana, 2025)
Geothermal energy, as one of the renewable energy sources, has great potential in Indonesia, which is located on a volcanic path and has abundant resource availability. However, the use of geothermal energy in Indonesia is still far from optimal, amid increasing dependence on fossil fuels and challenges in meeting energy needs in a sustainable manner. This article presents a normative juridical analysis that identifies the legal provisions governing the management of geothermal energy, including Law Number 21 of 2014 and its derivative regulations. Through a case study of Decision Number 529/Pdt.G.ARB/2018/PN. JKT. SEL, this article explores how the law is applied in resolving disputes that arise related to geothermal management. The results of the analysis show legal uncertainties that can hinder investment and development in the renewable energy sector. In addition, the issue of transparency in decision-making and resource management is also raised as an important factor that affects public trust. From the results of the analysis, the need for regulatory reform, increased transparency, and strengthening cooperation between the government and the community to ensure fairer and more sustainable management. With a holistic and integrative approach, it is hoped that the development of geothermal energy can contribute to the national energy transition and the fulfillment of sustainable energy needs in Indonesia.